Contextual Teaching and Learning (CTL) Approach to Science Learning Outcomes in Grade 4 Elementary Schools: Pendekatan Pembelajaran Contextual Teaching and Learning (CTL) Terhadap Hasil Belajar IPA pada Kelas 4 Sekolah Dasar - Nadhiroh, Siti; Efendi, Nur (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the effect of the Contextual Teaching and Learning (CTL) learning approach on science learning outcomes in class IVB at SDN Katerungan. This study uses an experimental quantitative research method with a one group pretest-posttest pattern. The instrument used is a learning outcome test sheet. Data collection techniques obtained from pretest-posttest. The data that has been obtained in this study were analyzed using the t-test and eta squared test. For the t-test the t-count value is 7,349 while the t-table value at a significant level of o,05 is 2,032, the the t-count value is greater that t-table (7,349>2,032) so that Ho is rejected and Ha is accepted, while the results of the eta squared test, the result is 0,525, which is interpreted as the result of the eta squared test of 0,525>0,14 which indicates that there is a big influence. So it can be concluded that there is a significant effect of the Contextual Teaching and Learning (CTL) learning approach on science learning outcomes in class IVB at SDN Katerungan.